Demystifying the Prudential Carve-out: A proposal (2015)
This article explores how the broadest spirited exception in the framework of the World Trade Organization, commonly referred to as the prudential carve-out, could be applied without adding to or diminishing the rights and obligations of WTO Members. It argues that through the customary rules of interpretation of international law, the only standard applicable to the prudential carve out is that of a reasonable means to ends connection. However, this broad standard of review can be enriched by expert knowledge on financial and prudential regulation, given that the form of dispute settlement established in the Annex to Financial Services of the GATS provides a window for dissecting the concept of “prudential”. The AFS requires that an “expert panel” decide on controversies regarding financial and prudential issues, instead of the ordinary “highly qualified” WTO panel. The article draws on principles developed by the disciplines of micro- and macroprudential regulation to exemplify how expert knowledge can guide an otherwise vague standard of review.